47.3: A Novel Triangle Matching RGBW Algorithm. (4th October 2019) - Sun, Yan; Xi, Yanhui; Dai, Bin; Zhang, Xiaomang; Bi, Yuxin; Shi, Lingyun
Abstract : Last year we introduced a RGB‐to‐RGBW algorithm with minimized color distortion by keeping the color coordinate unchanged from the original color. Based on the similar principle, we optimized our method and proposed a more efficient color mapping algorithm according to the triangular color gamut of RGBW display. The algorithm mainly consists of three steps. Step 1: Image Enhancement which is a preprocessing operation of input Image. Step 2: Pixel Analysis which can obtain CIE chromaticity coordinates (x, y) and luminance (Y) of the input RGB data. Step 3: Triangle Matching which is the core of this algorithm that can calculate the values of the output RGBW signal according to the triangular gamut enclosed by RGBW display. The results indicated that our algorithm has superior performance upon conventional method and is more flexible in application.